Projeto de um tribômetro para ensaios de desgaste e atrito por deslizamento sob múltiplas geometrias de contato - Maldaner, Fernando Henz (2023)
Wear is one of the main failure modes of engineering materials, responsible for considerable efficiency losses in mechanical systems. To evaluate the tribological behavior of materials subjected to sliding contacts, mechanical wear and friction tests are employed. These tests are conducted using equipment called tribometers, which generally have a high cost, as they are imported products. Due to their constructional characteristics and employed technologies, many commercial tribometers have functionalities that do not meet the needs of their users. Additionally, considering that different types of contact are developed in mechanical systems, reproducing these contacts through bench tests to evaluate the tribological performance of the involved materials requires the adoption of different equipment, increasing the cost of this characterization. Based on this problem and after identifying a set of needs related to the product, users, and test execution, the objective of this work was to develop, manufacture, and validate a tribometer for conducting sliding wear and friction tests, integrated with multiple contact configurations in a single test bench. In order to carry out the activities related to the development of the product in question, a product development methodology derived from the concepts presented by Pahl & Beitz was adopted. The developed tribometer consists of four assemblies, which, in conjunction with their respective subassemblies and components, allow for the evaluation of wear and friction performance of different sample configurations. The equipment is capable of performing four test configurations on the same test platform: wear tests in sphere (and pin) on disk, sphere (and pin) on plate - reciprocating, point contact fatigue, and scratch tests. The equipment is also equipped with resources that enable remote control of operational parameters and adaptive control, as well as automatic reading of output parameters from the test. Its programming interface consists of a 4.3-inch LCD screen interfaced to an Arduino platform, which allows for easy programming, control, and data acquisition of the test. Validation tests confirmed its accuracy, robustness, operability, and reliability, showing that the developed equipment meets the needs of its users, with the additional advantage of significantly lower cost compared to its commercial counterparts.